Состояние проблемы учета динамических процессов в расчетах дорожных одежд автомобильных дорог на прочность - Alyona Yurjevna Bazhenova; Aleksandr Vladimirovich Smirnov (Вестник СибАДИ)
Background of a single method for motor road pavement structural strength calculations when dynamic processes are being excited by traffic live load is considered in the article. The necessity of ten parameters and indices to be considered in calculations of pavements is shown. In this case the dynamic analysis becomes more complex but the data on dynamic processes in each layer of a multilayer pavement structure turns to be more adequate. The adequacy is obtained by determining parameters and indices in the process of load application, with the time step being from 0.1 to 0.001 from the beginning of loading.